1976
DOI: 10.1099/00222615-9-2-211
|View full text |Cite
|
Sign up to set email alerts
|

The importance of prolonged incubation for the synthesis of dimethylnitrosamine by enterobacteria

Abstract: THE experimental demonstration that nitrosamines are carcinogenic, mutagenic and teratogenic (Magee, 1969) has raised the question of their potential danger to man, and prompted studies of the circumstances that might expose him to them. Nitrosamines have been found in a limited number of foods for human consumption (International Agency for Research on Cancer, 1972), and have been shown to be produced by bacteria that occur in food (CollinsThompson et al., 1972;Fong and Chan, 1973). They may be produced in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

1978
1978
1996
1996

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…Thus, nitrosation activity catalyzed by nitrate reductases appears to be required for endogenous formation of O 6 -meG. Elevation of bacterial nitrosation in resting cells (11,20) correlates well with increased spontaneous mutagenesis under this growth condition. Moa mutants also lack several other molybdoenzymes, for example, trimethylamine oxide reductase, which reduces trimethylamine oxide to trimethylamine during anaerobic growth (3).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, nitrosation activity catalyzed by nitrate reductases appears to be required for endogenous formation of O 6 -meG. Elevation of bacterial nitrosation in resting cells (11,20) correlates well with increased spontaneous mutagenesis under this growth condition. Moa mutants also lack several other molybdoenzymes, for example, trimethylamine oxide reductase, which reduces trimethylamine oxide to trimethylamine during anaerobic growth (3).…”
Section: Discussionmentioning
confidence: 95%
“…At physiological pH values, nitrosation can be catalyzed by bacterial enzymes (8). For example, dimethylamine and nitrate or nitrite incubated with intact stationaryphase E. coli cells at pH 7 or 8 yielded detectable amounts of dimethylnitrosamine (11,20). Also, E. coli incubated in the presence of monomethylamine and nitrite appeared to be induced for the adaptive response to alkylating agents, indicating that a methylating agent was generated (47).…”
Section: Discussionmentioning
confidence: 99%
“…The end product(s) of these microbial reductions of N03 and NO2was not identified. Other investigators have found bacteria capable of forming N-nitroso compounds, from the precursor compounds, both in vitro (5,20) and in vivo (11); however, the amounts formed were low. This suggests that some other compounds, such as ammonia, could be formed in the CV intestinal tract.…”
Section: Discussionmentioning
confidence: 97%
“…The medium was adjusted to pH 7-4 and sterilised by filtration through sintered glass. Undefined medium, culture conditions, and measurements of growth were described by Coloe and Hayward (1976).…”
Section: Methodsmentioning
confidence: 99%